Песенный язык и семантика: критерии метра, рифмы, интонации (на белорусском материале) - Кутырёва-Чубаля, Г. (Народна творчість та етнографія, 2008)
Semantic potential of rhyme, metre and intonation is being investigated in this article. The analysis includes various genres of calendar and wedding songs. On the basis of the Belarus harvest songs the author of the article compares three rhythm and intonation types of agricultural incantations. These three types are ancient Belarus incantations which present the oldest three areas of folk songs.